FIBROESOPHAGOSCOPY IN THE CHOICE OF TREATMENT TACTICS CHEMICAL BURNS OF THE FOOD BREEDER IN CHILDREN - Tilavov U.H; Hotamov H.N; Chuliev M.S (Western European Studies, 2024)
Strictures of various genesis are the most common surgical pathology of the esophagus in children. In turn, up to 60-70% of them for many decades are cicatricial stenosis developed after chemical burns. Moreover, their number is not only not decreasing, but is even increasing due to the wide spread of new chemical compounds in everyday life
Keywords: various; increasing; spread